Muscle strain and cardiovascular stress in fencing competition - Li, J. X.; So, R. C.; Yuan, Y. W.; Chan, K. M. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Fencing is thought to be a highly technical sport, which requires both quick and accurate body movements. In addition good cardiovascular function is important. Studies examining the response of cardiovascular and skeletal muscle systems in fencing are less. This study was to examine the muscle strain and cardiovascular stress in fencing competition by monitoring heart rate (HR), blood lactate level during fencing competition, and the plasma creatine kinase (CK) activity in the day following. A total of 12 female epee fencers of national level participated in the study. A competition was organized among the participants. The resting values of heart rate were measured and the lactate and CK of venous blood were analyzed before the competition. During the competition, heart rate of fencers was recorded continuously by Polar Vantage NT and Polar Sport Tester watches. The blood lactate levels was assayed at 1 and 3 min after every bout of fight. The activity of plasma CK was examined 1 day after the match. The results showed that the percentage distribution of heart rate at above 75% maximal heart rate in the period of competition was 60% on average, the highest heart rate in fencers ranged from 167 to 191 beats/min. The highest value of blood lactate, 5.29 mM was detected in one fencer. However less than 4.0 mM was detected in most fencers. The plasma CK activity (average 289 u/l) significantly increased after the day of competition compared with normal range of the physiological condition (p<0.05). It is concluded that fencing competition produces relative high degree of strain on cardiovascular and skeletal muscle systems and specifically requires high capacity of muscle contraction. Therefore, enhancement of muscle function should be concerned in fencing training.